Survival Benefit of Combination Chemotherapy in Elderly Patients With Metastatic Pancreatic Ductal Adenocarcinoma. (August 2020) - Xie, Hao; Liu, Junjia; Ogden, John R.; Yin, Jun; Jatoi, Aminah; Hubbard, Joleen M.; McWilliams, Robert R.; Mahipal, Amit; Petersen, Gloria M.; Bekaii-Saab, Tanios S.; Ma, Wen Wee
Abstract : Objectives: Survival benefit of combination over single-agent chemotherapy for metastatic pancreatic ductal adenocarcinoma (PDAC) was demonstrated in younger patients in clinical trials. The authors aimed to evaluate whether this survival benefit of combination chemotherapy is present in elderly patients with metastatic PDAC. Materials and Methods: The authors identified elderly patients (age 65 y or older) with stage IV PDAC and extracted available clinical information from a prospectively maintained institutional pancreatic cancer registry from 2007 to 2016. The primary endpoint was overall survival. Cox proportional hazards regression was used for multivariable survival analyses. Survival outcomes for the entire cohort and by age group I (elderly, 65 to 75 y) and age group II (very elderly, older than 75 y) were assessed. Results: A total of 606 patients were included with a median age of 73.8 years. Among them, 239 patients (39%) received combination chemotherapy and 152 patients (25.1%) received single-agent chemotherapy as first-line treatment. Combination chemotherapy was associated with significantly longer median overall survival compared with single-agent chemotherapy (10.9 vs. 7.5 mo, P <0.001) with hazard ratio 0.62 (95% confidence interval, 0.47-0.81; P =0.001) after adjusting for age, sex, comorbidity, Eastern Cooperative Oncology Group (ECOG) performance status, and carbohydrate antigen 19-9 level. Analyses by age groups indicated that very elderly patients (age group II) benefited from combination chemotherapy compared with single-agent chemotherapy with hazard ratio 0.56 (95% confidence interval, 0.31-1; P =0.049), comparable with the age group I ( P age-treatment interaction =0.81). Conclusion: Elderly patients, even those older than 75 years, with metastatic PDAC benefited from combination chemotherapy. Abstract : Supplemental Digital Content is available in the text.